Tratamento de planta matriz com bioestimulante e enraizamento de estacas de goiabeira (Psidium guajava L.) ‘Século XXI’, sob concentrações de ácido indolbutírico - Pereira, Caíke de Sousa (2022)
The use of biostimulants can be an efficient alternative for improving the physiological and nutritional characteristics of guava (Psidium guajava L.), considering that they are rich in substances that act in the formation of enzymes, hormones and chlorophyll, favoring the plants in the process. absorption of water and nutrients. Therefore, the objective of the present study was to evaluate the physiological processes of guava matrix plants, cultivar Século XXI, submitted to doses of the biostimulant VIUSID Agro®, as well as to verify if there is a synergistic effect of the application of this product in the guava matrix with indolebutyric acid, in promoting the rooting of herbaceous cuttings. Two chapters were developed for the research: in I - the experimental design used was in randomized blocks, in a split plot scheme in time 3 x 4 (VIUSID Agro® x Time), with the plot constituted by the doses of VIUSID Agro® (0 ; 1 ml.3 L-1; 2 ml.3 L-1) and the subplots the number of applications of the product (2, 3, 4 and 5 applications), with four replications, composed of one plant per replication; in II - the treatments were arranged in a 3 x 5 factorial arrangement, the factors being doses of the biostimulant VIUSID Agro® (0; 1.0 and 2.0 ml.3 L-1 of solution) and concentrations of indolebutyric acid (0; 1,000; 2,000; 3,000 and 5,000 mg L-1). The experimental design used was completely randomized (DIC), with three replications, and the experimental unit consisted of 10 cuttings. In chapter I, variables such as: survival of cuttings, rooted cuttings, live cuttings without root, cuttings with callus, leaf retention, mortality, number of roots, root length, shoot, root and total dry mass were evaluated. In chapter II, gas exchange variables were evaluated: net assimilation rate, stomatal conductance, CO2 concentration in intercellular spaces, transpiration, leaf temperature, water use efficiency, intrinsic water use efficiency and instantaneous carboxylation efficiency; and fluorescence variables: initial fluorescence, maximum fluorescence, variable fluorescence, the ratio, quantum yield of photosystem II and chlorophyll a, b and total content. Finally, it was possible to conclude in chapter I: The gas exchange variables were favored by the use of VIUSID Agro®, with the exception of the instantaneous carboxylation efficiency (EiC); plants treated with a dose of 1.0 ml.3 L-1 of the biostimulant were more efficient in controlling leaf temperature; this same dose also positively influenced the chlorophyll “a” fluorescence variables, while the dose of 2.0 ml.3 L- 1 caused negative responses in plants. Therefore, it is recommended to use the biostimulant VIUSID Agro® for the cultivation of guava matrices, especially at a dose of 1.0 ml.3 L-1. Chapter II: Plants treated with VIUSID Agro® obtained higher percentage of rooted cuttings, root length, number of roots and root dry mass; cuttings treated with the dose of 1.0 ml.3 L-1 of the biostimulant and the concentration of 5,000 mg L-1 of the IBA obtained greater root dry mass. A synergistic interaction was observed between VIUSID Agro® and the plant hormone AIB, therefore, the use of the biostimulant at a dose of 1.0 ml is recommended. 3 L-1 together with AIB at a concentration of 5,000 mg L-1 for the formation of guava seedlings.